A conceptual privacy framework for privacy-aware IoT health applications - Thinakaran, Kavenesh; Jaspaljeet, Singh Dhillon; Gunasekaran, Saraswathy Shamini; Lim, Fung Chen (2017)
Internet of things (IoT) is intensely gaining reputation due to its necessity and efficiency in the computer realm.The support of wireless connectivity as well as the emergence of gadgets alleviates its usage essentially in governing systems in various fields.Though these systems are ubiquitous, pervasive and seamless, an issue concerning consumers’ privacy remains debatable. This is most evident in the health sector, as there is an immaculate rise in terms of awareness amongst patients where data privacy is concerned. In this paper, we propose a framework modelling the privacy requirements for IoT-based health applications.We have reviewed several privacy frameworks to derive at the essential principles required to develop privacy-aware IoT health applications.The proposed framework presents important privacy requirements to be addressed in the development of novel IoT health applications.